1998
DOI: 10.1007/pl00005289
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of nitric oxide-mediated relaxations in anaesthetized autoperfused streptozotocin-induced diabetic rats

Abstract: This work was designed to determine in vivo the influence of the metabolic control of streptozotocin-induced diabetic rats, measured by the levels of haemoglobin glycosylation in blood (HbA1c), on developing vascular endothelial dysfunction. For this, the vasoactive responses to basal and stimulated endothelial nitric oxide (NO) were studied using the technique of the anaesthetized autoperfused rat, analyzing the responses to acetylcholine (ACh) and N(G)-nitro-L-arginine methyl ester (L-NAME) in non-diabetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 53 publications
9
26
1
1
Order By: Relevance
“…Therefore we measured in vivo peripheral endothelial function in the femoral artery and ex vivo endothelial function in isolated aortic rings. In agreement with our previous studies [11,16] and with that of others [18] we also demonstrated under both in vivo and ex vivo conditions the presence of an impaired endothelial function under streptozotocin-diabetic conditions. Under diabetic conditions, endothelial dysfunction is a phenomenon that is often recognised in clinical and experimental settings [28,29].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore we measured in vivo peripheral endothelial function in the femoral artery and ex vivo endothelial function in isolated aortic rings. In agreement with our previous studies [11,16] and with that of others [18] we also demonstrated under both in vivo and ex vivo conditions the presence of an impaired endothelial function under streptozotocin-diabetic conditions. Under diabetic conditions, endothelial dysfunction is a phenomenon that is often recognised in clinical and experimental settings [28,29].…”
Section: Discussionsupporting
confidence: 94%
“…In vivo assessment of vascular function and left ventricular BP in vivo For in vivo assessment of vascular function, we used the autoperfused hindlimb model in the rat as described previously [16][17][18]. Briefly, the rats were anaesthetised (chloral hydrate, 400 mg/kg body weight, i.p.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Defective endothelium-dependent relaxation was restored 4 weeks after pancreatic transplantation, performed in rats after 12 weeks of diabetes (Pieper et al, 1998a). A close relationship between endothelial dysfunction and metabolic control was found in streptozotocin-diabetic rats in which the degree of hyperglycaemia was manipulated with subcutaneous insulin implants (Angulo et al, 1998). Conversely, acute exposure to high glucose concentrations induces endothelial dysfunction similar to that in diabetic animals (Tesfamariam et al, 1990;Tesfamariam & Cohen, 1992;Bohlen & Lash, 1993;Mayhan & Patel, 1995).…”
Section: Aetiology Of Endothelial Dysfunction In Diabetesmentioning
confidence: 77%
“…In accordance, an increased NO synthase activity, measured by conversion of 3 H-L-arginine to 3 H-L-citrulline, was demonstrated in diabetic rat heart endothelium (RoÈ sen et al, 1996). Exogenous L-arginine (partially) restored endotheliumdependent vasodilatation in certain (Pieper & Peltier, 1995;Fulton et al, 1996;Matsunaga et al, 1996;Angulo et al, 1998), but not all studies (Heygate et al, 1995;Koltai et al, 1997;Mayhan et al, 1997). These variable results may relate to an aspeci®c e ect of L-arginine: this amino acid is known to release insulin, which by itself may stimulate endothelium-dependent vasodilatation (MacAllister et al, 1995).…”
Section: Mechanisms Of Impaired Endothelium-dependent Vasodilatation mentioning
confidence: 99%
See 1 more Smart Citation